Industrial proteins in perspective - Aalbersberg, W. Y. (Willem Ysbrand) (Progress in biotechnology, 2003)
This book gives the state of the art of the application of industrial (bulk) proteins in the manufacture and the resulting properties of various products, both in manufactured foods and in non-food applications. This concerns the making of gels, emulsions, foams and various specific products, including photographic films, tissue replacers and adhesives. Internationally known experts discuss the progress made over the last two decades in the study and the industrial application of a wide variety of proteins. It will help R & D departments in the industry, including producers and users of bulk proteins, in finding new functional applications of industrial proteins and in improving the quality of existing processes and products. It is the desired functional properties in industrial application of proteins that primarily determine their market value.